Assessment and treatment of muscle imbalance : the Janda approach - Page, Phil, ....-; Frank, Clare, ....-; Lardner, Robert, ....- (Champaign : Human Kinetics, 2010)
Assessment and Treatment of Muscle Imbalance: The Janda Approach blends postural techniques, neurology, and functional capabilities in order to alleviate chronic musculoskeletal pain and promote greater functionality. Developed by Vladimir Janda, respected neurologist and physiotherapist, the Janda approach presents a unique perspective to rehabilitation. In contrast to a more traditional structural view, the Janda approach is functional, emphasising the importance of the sensorimotor system in controlling movement and chronic musculoskeletal pain syndromes from sports and general activities. This is the only text to offer practical, evidence-based application of Janda's theories. Filled with illustrations, photos and step-by-step instructions, the book uses a systematic approach in presenting information that can be used in tandem with other clinical techniques. This resource for practitioners features a rationale for rehabilitation of the musculoskeletal system based on the relationship between the central nervous system and the motor system. Through this book, it provides an evidence-based explanation of muscle imbalance. The step-by-step Janda system of evaluation is explained including analysis of posture, balance and gait; evaluation of movement patterns; testing of muscle length; and, assessment of the soft tissue. The text explores treatment options for muscle imbalance through facilitation and inhibition techniques and sensorimotor training to restore neuromucular function. It also includes four case studies examining musculoskeletal conditions and showing how the Janda approach compares with other treatments. This text combines theory, evidence and applications to assist clinicians in implementing the Janda approach into their practice.